COMPARATIVE ANALYSIS OF CHANGES IN THE HYDROTHERMAL COEFFICIENT, PEDA INDEX AND POTENTIAL NECTAR PRODUCTIVITY OF SMALL-LEAVED LINDEN GROWING IN DIFFERENT NATURAL-CLIMATIC ZONES OF THE REPUBLIC OF BASHKORTOSTAN (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The study is aimed at identifying the relationships between the natural and climatic conditions of small-leaved linden growth sites and their nectar productivity. During a comparative assessment of the nectar productivity of small-leaved linden plantations and hydrometeorological data (hydrothermal coefficient (HTC), Pedya Aridity Index) from 2018 to 2023 in the territories of protected areas located in different natural and climatic conditions of the Republic of Bashkortostan, it was found that in 2019 there were the most optimal conditions for nectar secretion of linden plantations. In the fall of 2018, according to the Pedya Index, it was noted that in the Zilim Nature Park, during the entire warm period, there were "normal moisture conditions", which made it possible to obtain maximum nectar production in 2019 under conditions of optimal moisture supply (HTC = 1.81) was 397.2 ± 39.7 kg/ha. In the Shaitan-Tau Nature Reserve in 2019, during the linden flowering period, drought conditions observed, according to the Pedya Index, and nectar production was only 232.8 kg/ha. Optimal hydrothermal conditions allow plants to develop well and produce more nectar. Hydrometeorological indicators of the previous year can be used to predict potential nectar productivity in the current year. For example, if the previous year was wet and warm, this can have a positive effect on flowering and nectar secretion in the current year.
Keywords: nectar productivit; linden; hydrothermal coefficient; Pedea index